The Oxford handbook of science and medicine in the classical world - Keyser, Paul T.; Scarborough, John (Oxford handbooks online, 2018)
With essays introducing, surveying, summarizing, and analyzing the many sciences of the classical world, readers are invited to study these fascinating disciplines, and in many cases offer new interpretations and syntheses. There is a brief section on Greek science of the 6th through 4th centuries BCE, then a long section on Greek science of the Hellenistic era, the period in which ancient Greek science was most active. The early Roman Empire is treated in a fourth section, and the final section addresses the sciences of Late Antiquity, or Early Byzantine, period, the 4th through 7th centuries CE. Throughout, the volume insists on the close integration of the ancient sciences with one another and on the consequent necessity to study them as a whole, not in isolation. Each essay includes a bibliography supporting its content and providing further reading. Key figures in the history of ancient science, each receive their own essay.